2015
DOI: 10.3989/mc.2015.10613
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for assessing the valorization of a waste into cementitious material: dredged sediment for production of self compacting concrete

Abstract: This article presents some guidelines in order to analyse the feasibility of including a waste material in the production of a structural cementitious material. First of all, the compatibility of the waste with a cementitious material has to be assured; then, if necessary, a decontamination step will be carried out; after, decision on the type of material has to be taken based on different aspects, with special emphasis on the granulometry. As a last step, mechanical, environmental and durability properties ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Since CB, MB and SW have similar reactivity and considering the replacement level (8,24 and 40% w/w) by ceramic waste, in general, the emission in 72, 216 and 360 g CO 2 / kg cement could be reduced, respectively. Portland blended cements: demolition ceramic waste management • 7 In 2014, according to the Association of Portland Cement Manufacturers in Argentina (AFCP) (31), 11,438,165 t of cement were exported to the domestic market.…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Since CB, MB and SW have similar reactivity and considering the replacement level (8,24 and 40% w/w) by ceramic waste, in general, the emission in 72, 216 and 360 g CO 2 / kg cement could be reduced, respectively. Portland blended cements: demolition ceramic waste management • 7 In 2014, according to the Association of Portland Cement Manufacturers in Argentina (AFCP) (31), 11,438,165 t of cement were exported to the domestic market.…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…In fact, Silica fume (SF) increases the cement cohesion and compressive resistance because it has a higher specific surface than metakaolin and cement, other studies confirmed these results and indicated that the use of metakaolin and Silica fume (SF) could increase the compressive resistance [9,[15][16][17]. Several experimental researches were conducted in recent years to investigate the effect of regular, volcanic, waste aggregate materials on different properties of self-compacted concrete [18][19][20][21]. Although there are acceptable studies about Silica fume (SF) and metakaolin, but there is only limited studied about the use of both of them simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Beside economic, there are also important environmental benefits by using industrial by-products. Also, data regarding the use of waste and cementitious materials in SCC was analyzed in previous study, show that industrial waste is among the most prominent (15). Namely, the design of SCC allows usage of industrial and building wastes in case of producing SCC with the same or better engineering properties (6,14,16,17), while the purpose of using powdered waste industrial residues is to ensure sustainable production of SCC and to produce "green concrete" (6,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%